STRATEGY OF ONLINE BEGGARS ON TIKTOK IN ATTRACTING SYMPATHY AND DONATIONS FROM THE AUDIENCE - Gultom, Imel Parida; Daud, Daud (Dinamika Bahasa dan Budaya, 2025)
This study examines the strategies used by online beggars on TikTok to gain sympathy and donations from audiens, as well as the resulting social and economic impacts. The phenomenon has emerged alongside the growth of social media, particularly TikTok’s live streaming feature, which allows users to receive virtual gifts as donations. This research employs a qualitative method using a virtual ethnography approach. Data were collected through content observation and in-depth interviews with six informants actively conducting live broadcasts. The finding reveal that online beggars utilize various strategies such as coin battles, emotional storytelling, performing challenges, and involving children during live strams. These tactics are intended to foster emotional connection and provoke audiens sympathy. The analysis is guided by Pierre Bourdieu’s theory of social practice, including the concepts of habitus, social and symbolic capital, and the dynamics of the digital arena. Economically, some informants earn significant income used for daily needs or small businesses. However, socially, the practice raises controversy due to its potentially manipulative. Thus study offers insights into emerging digital social realities and highlights the need for regulation regarding online begging practices on social platforms. Keywords: TikTok, Online Beggars, Strategy, Sympathy, Donation